Home background and secondary school students’ academic performance in Islamic Studies in Oyo North, Nigeria - Jamiu, Abdur-Rafiu; Ajidagba, Uthman Abdulrahman; Bolaji, Azeez Hussein (Penerbit Universiti Kebangsaan Malaysia, 2021)
The role played by home as an agent of civilization could not be overemphasized. Home is a determining factor in any child’s behaviour and thus influences his academic performance. Hence, this study examined home background and secondary school students’ academic performance in Islamic Studies in Oyo North, Nigeria. The study was a descriptive research of a survey type, stratified sampling technique was used to select 500 respondents. A researcher-designed questionnaire and Performance Test were used to elicit information from the respondents. Mean, standard deviation and chi-square were used to test the hypotheses at 0.05 level of significance. The findings revealed that there was a significant influence of home background on secondary school students’ academic performance in Islamic studies; there was a significant effect of parents’ level of education on secondary school students’ academic performance; there was a significant effect of parents’ level of occupation on secondary school students’ academic performance; there was a significant influence of parental care and commitment on secondary school students’ academic performance; it was concluded that home status, parental educational background, parents’ occupation, school type, home supports for children’s education, parental care and commitment have a significant influence on secondary school students’ academic performance. It was recommended that parents and guardians should endeavour to play their parental roles to ensure good upbringing of their children. Islamic Studies teachers should take cognizance of the various backgrounds of their students in the classroom thereby employing methods and techniques of teaching that would cater for those background differences.